Analysis of room attendant service quality in increasing customer satisfaction at Hotel Vila Lumbung - Ni Kadek Ulan Prasiska Yanti; I Gusti Made Wendri; I Ketut Suarja; Ida Ayu Elistyawati (Journal of Applied Sciences in Travel and Hospitality, 2022)
This study discusses the analysis of the service quality of room attendants in increasing customer satisfaction at Hotel Vila Lumbung. The purpose of this study is to determine the level of guests’ satisfaction with the services provided by the room attendant and determine the service indicators that need to be improved and maintained by the room attendant at this hotel. The sample is 80 respondents. This study uses a sampling technique that is incidental random sampling. The analysis technique used is SERVQUAL analysis (Service Quality) and Importance Performance Analysis (IPA). The result shows there are sixteen indicators found in the five dimensions of the service quality that show the room attendants’ performance are already categorized as excellent in terms of such dimensions as tangibility, reliability, assurance, and empathy. This indicates that there is only one dimension which service is still need to improve and maintain to make customer satisfied, namely the responsiveness dimension found in quadrant A in IPA.